Controle de qualidade das embalagens de leite na indústria Betânia - Rodrigues Filho, José Elinesio Rocha (Universidade Federal Rural do Semi-Árido, 2021)
With globalization, changes in lifestyle and eating habits, the problems related to food quality have become more evident. The quality control of a food industry must act to ensure the safety, identity, quality and integrity of its products, through a set of parameters that allow characterizing the specifications of a product in relation to a desirable or defined standard, regarding its intrinsic and extrinsic factors, hygienic-sanitary and technological, for such the packaging has the function to ensure the integrity and preservation of products until the end of their shelf life, thus being an object of evaluation of the quality control of a food industry. To ensure the safety of the product, the packaging must maintain hermeticity until the final consumption, i.e., free of defects that allow the product to come into contact with the external environment. Thus, it was possible to verify that the company in which the supervised internship was carried out is committed to the quality control of its processes and products, in addition to complying with the Normative Instructions, Ordinances and Decrees of the Ministério da Agricultura, Pecuária e Abastecimento.
Keywords: Controle de qualidade; Leite; Hermeticidade das embalagens; Qualidade dos alimentos; Quality Control; Milk; Hermeticity of Packages; Quality of food; ENGENHEARIAS::ENGENHARIA QUIMICA